2018
DOI: 10.3892/mmr.2018.9282
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 receptor regulates EMMPRIN and MMP‑9 expression through AMPK/MAPK signaling in PMA‑induced macrophages

Abstract: The rupture of atherosclerotic plaques may result in the formation of thrombi, which may induce subsequent cardiac events such as acute myocardial infarction. Overproduction of matrix metalloproteinases (MMPs) and extracellular matrix metalloproteinase inducers (EMMPRINs) by monocytes and macrophages may lead to rupture of atherosclerotic plaques as a result of the degradation of the extracellular matrix. The purinergic 2X7 receptor (P2X7R) is expressed in macrophages that are assembled in atherosclerotic lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Consequently, inhibiting EMMPRIN and MMP-9 levels can be beneficial for the stability of atherosclerotic plaques. Notably, we previously revealed that P2X7R effectively regulates both EMMPRIN and MMP-9 during monocyte differentiation into macrophages (Lin et al, 2018). In this study, we demonstrated that P2X7R was upregulated under oxLDL stimulation in macrophages and that its inhibition significantly reduced EMMPRIN and MMP-9 expression, which indicates that P2X7R is a regulator of EMMPRIN and MMP-9 and could be a potential therapeutic target for inhibiting plaque rupture or retarding atherosclerosis.…”
Section: Discussionmentioning
confidence: 51%
“…Consequently, inhibiting EMMPRIN and MMP-9 levels can be beneficial for the stability of atherosclerotic plaques. Notably, we previously revealed that P2X7R effectively regulates both EMMPRIN and MMP-9 during monocyte differentiation into macrophages (Lin et al, 2018). In this study, we demonstrated that P2X7R was upregulated under oxLDL stimulation in macrophages and that its inhibition significantly reduced EMMPRIN and MMP-9 expression, which indicates that P2X7R is a regulator of EMMPRIN and MMP-9 and could be a potential therapeutic target for inhibiting plaque rupture or retarding atherosclerosis.…”
Section: Discussionmentioning
confidence: 51%
“…Also, knocking out P2X7R inhibits pulmonary fibrosis (Liu et al, 2015), and P2X7R levels contributes to the release of MMP9, an important mediator of myocardial remodeling (Riteau et al, 2010). And our previous research showed that the inhibition of P2X7R downregulated both EMMPRIN and MMP9 expression (Gu and Wiley, 2006; Yabluchanskiy et al, 2013), and reduced NLRP3 inflammasome activation in PMA-induced macrophages (Lin et al, 2018). Intriguingly, inflammatory factors such as TNF-α induce MMP9 activity (Kong et al, 2016), which promote the activation of TGF-β that subsequently enhances the synthesis of collagen I and deregulates collagen turnover, resulting in the development of fibrosis in the heart.…”
Section: Discussionmentioning
confidence: 98%
“…Panx1 was also involved in regulating ATP release, which can activate apoptosis or autophagy signaling (17,18). Extracellular ATP can act as a paracrine molecule to activate P2X7R, which can regulate various signaling pathways, such as the AMPK and MAPK signaling pathway (43). Previous studies have shown that ferroptosis could activate the MAPK pathway through MEK (20).…”
Section: Panx1 Mediates Ferroptosis In Iri-akimentioning
confidence: 99%